The interplay between microbial dysbiosis and immune dysfunction with age - Thevaranjan, Netusha (My University, 2016)
It is well known that the elderly often manifest chronic low-grade inflammation. This phenomenon, called “inflamm-aging,” is postulated to contribute to increased susceptibility towards infectious diseases and an overall increase in frailty. We have proposed examining the gut microbiome as a potential mediator of these changes. Gut microbial communities influence the host immune system; often dictating an individual’s health status. Thus, harmful gut microbiome changes, termed dysbiosis, are associated with poor health in the elderly. We first sought to understand the key immunological, physiological and microbiome changes occurring with age (Chapter 3). Our data reveals immune impairments in aged mice, with increased intestinal permeability, systemic inflammation and alterations in the functions of myeloid cell populations. However, our aged germ-free (GF) mice are protected from these outcomes, indicating that the old microbiome may play a strong role in these age-associated impairments. To study this further, we have colonized young and old GF mice with the “young” or “old” microbiota in order to determine whether the relationship between microbial dysbiosis with age and health status is correlative or causative (Chapter 4). Interestingly, young GF mice colonized with old microbiota have significantly increased permeability, systemic inflammation and an influx of Ly6Chigh monocytes when compared to those colonized with the young microbiota. By using transgenic mice (TNF-/- mice), or by reducing systemic TNF levels via therapeutics, we were able to reduce some aspects of microbial dysbiosis and age-associated inflammation (Chapter 5). Our data suggests that harmful changes to the gut microbiome composition with age initiate a cycle of negative events that ultimately result in increased inflammatory myeloid cell recruitment, increased intestinal permeability and an overall increase in systemic inflammation in old mice. By identifying these key changes, we can work towards developing effective therapeutics that promotes healthy aging and protection against infectious diseases.
Keywords: Microbiome; Immunology; Aging; Gnotobiotic; Gut permeability; Illumina Sequencing